Recent advances in the study of pre-slaughter stress factors on beef, poultry and pork quality - Irreño-Barrera, Francisco Javier (2022)
Stress in the pre-slaughter stage is a critical period in the production chain because it causes losses in animal live weight, affects carcass yield and quality, and leads to a loss of animal welfare due to an alteration in the homeostasis of the organism as a result of exposure to stressful situations. This review identifies and describes the stressors that have been reported in the last 5 years as the main causes of meat quality deterioration, including animal handling activities by farm or plant personnel (transport, loading and unloading, in the slaughter plant), environmental conditions (temperature, vibrations), waiting time prior to slaughter and mixing of lots, water and food fasting period, and fatigue states, as well as the biomarkers routinely used for the study of conditions associated with stress. Although research on the subject is abundant, the biochemical mechanisms involved in obtaining certain organoleptic characteristics of meat with respect to stress levels and the individual variations observable in different groups of animals are still not completely clear, and more research is needed on stress biomarkers that allow a more specific, effective and non-invasive identification and measurement.